Multifocal Electroretinogram Can Detect the Abnormal Retinal Change in Early Stage of type2 DM Patients without Apparent Diabetic Retinopathy - Jiang Huang; Yi Li; Yao Chen; Yuhong You; Tongtong Niu; Weijie Zou; Weifeng Luo (Journal of Diabetes Research)
Purpose. To study retinal function defects in type 2 diabetic patients without clinically apparent retinopathy using a multifocal electroretinogram (mf-ERG). Methods. Seventy-six eyes of thirty-eight type 2 diabetes mellitus(DM) patients without clinically apparent retinopathy and sixty-four normal eyes of thirty-two healthy control (HC) participants were examined using mf-ERG. Results. Patients with type 2 DM without apparent diabetic retinopathy demonstrated an obvious implicit time delay of P1 in ring 1, ring 3, and ring 5 compared with healthy controls (t=5.184, p≤0.001; t=8.077, p≤0.001; t=2.000, p=0.047, respectively). The implicit time (IT) in ring 4 of N1wave was significantly delayed in the DM group (t=2.327, p=0.021). Compared with the HC group, the implicit time of the P1 and N1 waves in the temporal retina zone was significantly prolonged (t=3.66, p≤0.001; t=2.187, p=0.03, respectively). And the amplitude of P1 in the temporal retina decreased in the DM group, which had a significantly statistical difference with the healthy controls (t=−6.963, p≤0.001). However, there were no differences in either the amplitude of the response or the implicit time of the nasal retina zone between DM and HC. The AUC of multiparameters of mf-ERG was higher in the diagnosis of DR patients. Conclusions. Patients with type 2 DM without clinically apparent retinopathy had a delayed implicit time of P1 wave in temporal regions of the postpole of the retina compared with HC subjects. It demonstrates that mf-ERG can detect the abnormal retinal change in the early stage of type2 DM patients without apparent diabetic retinopathy. Multiparameters of mf-ERG can improve the diagnostic efficacy of DR, and it may be a potential clinical biomarker for early diagnosis of DR.